1989
DOI: 10.1094/phyto-79-409
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Fitness Interactions in the Bean Rust Fungus

Abstract: Kardin, M. K., and Groth, J. V. 1989. Density-dependent fitness interactions in the bean rust fungus. Phytopathology 79:409-412.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
0
14
1
Order By: Relevance
“…Interestingly, Leonard and Mundt () also demonstrate that small differences in latent period have greater impact on disease epidemic rates than do small differences in either infection efficiency or spore production per pustule. Further, shorter latent periods may affect competition among pathogens for host resources (Kardin and Groth ; Baart et al. ; Lehman and Shaner ; Newton et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Leonard and Mundt () also demonstrate that small differences in latent period have greater impact on disease epidemic rates than do small differences in either infection efficiency or spore production per pustule. Further, shorter latent periods may affect competition among pathogens for host resources (Kardin and Groth ; Baart et al. ; Lehman and Shaner ; Newton et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sporulation is sometimes expressed in spore production per unit area of diseased leaf (Clifford & Clothier, 1974) or relative to lesion size (Miller et al , 1998). It has repeatedly been shown that spore production per lesion is highly density‐dependent (Kardin & Groth, 1989). It can be useful to consider the spore production per unit area of sporulating tissue (Hamid et al , 1982a; Subrahmanyam et al , 1983; Dowkiw et al , 2003), which is considerably less density‐dependent (Robert et al , 2004).…”
Section: Measuring Quantitative Components Of the Host–pathogen Intermentioning
confidence: 99%
“…Finally, some components of the pathogen life cycle (e.g. spore production per lesion) are strongly influenced by lesion density (Katsuya & Green, 1967; Mehta & Zadoks, 1970; Rouse et al , 1980; Kardin & Groth, 1989; Robert et al , 2004). These sources of variation are generally considered unwanted effects in aggressiveness measurements, but may account for a large portion of variability.…”
Section: Effects Of Environment On Expression Of Aggressiveness Compomentioning
confidence: 99%
See 1 more Smart Citation
“…As pathogen density and genotype frequency change during the course of an epidemic, relative fitness may change over time, perhaps even reversing the fitness ranking of simple versus complex genotypes. Though experimental data are few, examples exist of both density-dependent (62,65,126,130) and frequency-dependent (65,126) selection for competing genotypes of plant pathogens. Simulation modeling suggests that density-dependent effects can slow selection for complex races in host mixtures, though density-dependence did not prevent the complex genotype from eventually dominating the simulated pathogen populations (80,81).…”
Section: Alternative Mechanismsmentioning
confidence: 99%